Examining the Israeli Product Boycott in Indonesia: Exploring the Intersection of Religious Tensions and Digital Information to Assess its Influence on Global Discourse on Humanity - Afriani, Susi Herti; Darussalam, Darussalam; Musa, Kazi (Kitabina: Jurnal Bahasa dan Sastra, 2024)
This study examines the complex dynamics related to the Israeli product boycott in Indonesia. It explores the interaction between religious tensions and digital information to evaluate how it affects the worldwide conversation on humanity. The research primarily examines the linguistic strategies used in Indonesia to depict debates and conflicts between religions. It also investigates the influence of digital information on moulding public opinion over the boycott. By utilising Critical Discourse Analysis theory, this study aims to clarify the impact of conversation on international discussions regarding humanity and democratic dynamics. This research analyses the relationship between religious tensions, linguistic strategies, and digital information better to understand the broader consequences of the Israeli product boycott. It aims to uncover the potential impact of this boycott on global discussions about human rights and democratic values. The uniqueness of this study is not only in its thorough analysis of the Israeli product boycott but also in its theoretical advancements. This research presents an innovative approach that may be used for a wider range of socio-political phenomena by examining the interplay between religious conflicts, linguistic techniques, and digital information. This text sheds light on the particular situation under consideration. It presents a theoretical framework to analyse how these interconnected elements influence global conversations about human rights and democratic values.